Shaping future planners: insights from SULAM’s English teaching for aboriginal school children in Kampung Putra - Mohd Hanapiah, Mohamad Taufek; Ahmad, Raziah; Che Yusof, Muhammad Adam; Anyau, Eugenie (UiTM Press, 2025)
Integrating Service-Learning (SULAM) into planning education, particularly in the TPR512 Regional Planning and Development course, bridges academic theory and real-world practice. Despite its recognised benefits in community development, its specific impact on regional planning education and marginalised communities remains underexplored. This study examines how SULAM enhances students' planning competencies through engagement with the Temuan community in Kampung Putra, Jelebu, Negeri Sembilan, through teaching English. The key objectives are: first, to assess how hands-on experience improves students' practical skills and regional planning knowledge, and second, to evaluate the project's role in fostering essential soft skills like communication, teamwork, and civic responsibility by incorporating English teaching activities. Using a qualitative case study approach, findings highlight key challenges, including communication barriers (42.9%) and cultural differences (35.7%), underscoring the need for cultural sensitivity. Despite this, 100% of students reported a deeper understanding of regional planning, particularly in rural contexts. The project also emphasised interactive learning methods, with 60.7% of participants favouring games and participatory approaches through group activities. Supported by the Ministry of Higher Education (MOHE) and Universiti Teknologi MARA (UiTM), the SULAM project underscores how realworld engagement can enhance academic learning. While limited by sample size and duration, it underscores the value of service-learning in equipping future planners with adaptability and stakeholder engagement skills. Future research should explore its long-term impacts for broader application.